As políticas de desenvolvimento regional para a Amazônia como estratégia da modernização conservadora - REGO, Gilson Fernando de Jesus (Universidade Federal do Oeste do Pará, 2021)
This work explores the development of public policies directed toward Amazonian populations and the effects of such policies on the productive activities of these groups. To that end, it analyzes the implementation and outcomes of various regional development programs elaborated for the Amazon. It links these policies to conservative modernization strategies that both allow for the expansion of production and maintain the capitalist mode of production. This theme is pressing because over the last few decades a wave of form of occupation has proliferated across Amazon under the banner of regional development, which functions as an ideological mechanism to involve innumerable rural communities in these projects and to transform their territory into fertile ground for the advance of capital. The environmental damage and the social transformation that has occurred within these communities are characteristic of political interventions that seek to integrate those families in the logic of the market, reorganizing their productive relations to become part of the production chain demanded by the market. Thus, all of the groups incorporated by capital are involved in very different pedagogical programs in order to make them conform to the new model.